Características neuropsicológicas de agressores de crianças e mulheres - Silva, Ana Paula Jesus da (2022)
Women victims of gender violence suffer serious psychological damage, in addition to cognitive changes. Children, who live in an environment where violence thrives, also learn to use it as a way to solve their problems and they reproduce it intergenerationally. In this context, the importance of studying domestic and other aggressors is emphasized, with a view to verifying common characteristics among them. The possible existence of a neuropsychological profile of these aggressors might be useful in intervention programs which aim to reduce the recurrence of violence against women and children. Thus, the main purpose of this study was to validate personality characteristics and cognitive aspects in aggressors of children and women. This is a descriptive cross-sectional study with 292 participants aged over 18 years old, who were legally responsible for violence against women and children. The sample was organized into two groups: aggressors of women (n=75) and aggressors of children (n= 217) deprived of their liberty in prisons in the State of Paraná. Socio-demographic and criminal data and personality aspects were collected through Barrat Impulsivity Scale (BIS – 11) and the NEO FFI Personality Inventory, and the cognitive aspects were gathered using the Figure of Rey, Trail A and B, Five-digit test (FDT), Digits (WAIS-III), Attention Test D2-R, Verbal Fluency (F-A-S Test) and WMT-2 for the IQ. In relation to the aggressors of women, the average age was 40 years old, with incomplete elementary education. The victims were, in their majority, wives/partners and the prevalent violence was sexual in the form of rape (46%), followed by physical aggression (33%). In the sample related to aggressors of children, the average age was 50 years old with incomplete elementary education, with evidence of sexual violence with rape (49,8%) and sexual abuse (47%), with predominance of female victims (93%) with an average age of 10 years old and known to their aggressors (stepdaughters, daughters or granddaughters). As for the personality aspects, the two groups showed similar results with low levels of openness, high levels of conscientiousness, and failures in impulse control. The IQ (Intelligence Quotient) was lower than the classification considered within the limits of normality. Cognitive tests especially signaled difficulties in visuoconstructive skill, the capacity to plan before performing tasks and problem-solve strategies. Deficits in attention, mental flexibility and inhibitory control were impaired in both samples. The studies allow us to conclude that aggressors of women and children do have cognitive deficits, typical personality characteristics and life experiences marked by violence. Such factors in consonance can influence an individual to commit violence and easily relapse into crimes of the same nature. Therefore, there is a need for early interventions at the level of prevention with disruptive families where there are children who are victims of violence, but also the necessity for interventions more directed to the specificities of this public already in prison, responding accordingly to the retributive justice, which provides for deprivation of liberty, but little guarantees the desired rehabilitation.(AU)